Shrinking Violet - Best, Cari.; Potter, Giselle (New York : Farrar, Straus and Giroux, 2001)
Violet, who is very shy and hates for anyone to look at her in school, finally comes out of her shell when she is cast as Lady Space in a play about the solar system and saves the production from disaster.
"Melanie Kroupa Books."
Keywords: Bashfulness -- Fiction; Schools -- Fiction; Theater -- Fiction